2022
DOI: 10.46963/asatiza.v3i2.499
|View full text |Cite
|
Sign up to set email alerts
|

Pemanfaatan Media Belajar dalam Meningkatkan Prestasi Belajar Siswa

Abstract: This study aims to analyze how the use of learning media in relation to student achievement. Limited teaching resources, not all schools have source books, situations like this require teachers to learn illustration/visualization to provide available resources in the form of media. This type of research is library study, using the method of collecting data documentation by using books and journals as the main source. The data obtained are presented and analyzed so as to obtain interesting and scientific conclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
1
0
2
Order By: Relevance
“…The results of the literature study also found that practicum activities still need to be carried out (Rahmawati & Khamidinal, 2019). This is different from the essential competencies of the curriculum on colloidal material, which should introduce students not only to theoretical concepts but also to direct experience to hone science process skills (Ghozali, 2017). However, the limited knowledge of educators regarding the potential of local resources in the surrounding environment, facilities and infrastructure, human resources, costs, time, and other nontechnical constraints cause practicum to be rarely carried out (Candra & Hidayati, 2020).…”
Section: Introductionmentioning
confidence: 94%
“…The results of the literature study also found that practicum activities still need to be carried out (Rahmawati & Khamidinal, 2019). This is different from the essential competencies of the curriculum on colloidal material, which should introduce students not only to theoretical concepts but also to direct experience to hone science process skills (Ghozali, 2017). However, the limited knowledge of educators regarding the potential of local resources in the surrounding environment, facilities and infrastructure, human resources, costs, time, and other nontechnical constraints cause practicum to be rarely carried out (Candra & Hidayati, 2020).…”
Section: Introductionmentioning
confidence: 94%
“…3, Maret 2023 Variabel instrumentasi adalah validasi data angket. Alat survei diuji dengan menggunakan uji validitas-reliabilitas untuk memastikan bahwa kuesioner yang disiapkan dapat dipahami oleh responden dan ukurannya konsisten (Ghozali, 2017b). Metode analisis data yang digunakan adalah metode kuantitatif dengan menggunakan metode analisis data menggunakan rumus statistik melalui aplikasi statistik "SPSS 20".…”
Section: Operasionalisasi Variabelunclassified
“…Selain itu, siswa didorong untuk lebih mampu dalam mengobservasi, menanya, menalar dan mengomunikasikan atau mempresentasikan terkait hal yang dipelajari dari fenomena alam atau pengalaman langsung. 8 Adanya pendekatan ini diharapkan siswa menjadi lebih aktif dalam kegiatan belajar, materi yang dipelajari mudah dimengerti dan dipahami oleh siswa. Mengingat pentingnya peranan Pendekatan Saintifik dalam implementasi kurikulum 2013, maka pendekatan saintifik memungkinkan berpengaruh terhadap kemampuan pemecahan masalah siswa, dapat menciptakan suasana yang menyenangkan dalam proses kegiatan belajar mengajar dan menjadikan siswa lebih termotivasi untuk berpartisipasi aktif dalam mengemukakan ide-idenya dan berbagai pendapatnya.…”
Section: Latar Belakangunclassified